Voters (Dis)-Believing Digital Political Disinformation in Gubernatorial Election of DKI Jakarta 2016-2017 - Gilang Desti Parahita (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2018)
Some studies, with regards to the salience of digital disinformation, have focused on investigating the tendency to believe disinformation by looking at a single cluster of factors. This study reveals factors ranging from multiple clusters, such as socioeconomic status, political partisanship, diversity of media exposure, trust in the media, and the digital fluency of the voters. The Gubernatorial Election of DKI Jakarta during 2016-2017 provided a context for examining the correlation between these factors and the (dis)-belief of digital political disinformation among the voters. In the election, the incumbent governor, Basuki Tjahja Purnama, was falsely accused of being a communist, which is still a dirty word in Indonesia, by his opponent. A survey was conducted for this research, collecting completed questionnaires from 191 citizens of DKI Jakarta who had voting rights and could access the online and digital disinformation. The null hypothesis was that socioeconomic status, political partisanship, diversity of media exposure, trust in the media and digital fluency did not influence the citizens’ perceptions towards digital political information. However, the regression analysis found that the null hypothesis should be rejected. Of those predictors, political partisanship had the highest significant correlation with those perceptions.